2019
DOI: 10.1353/lib.2019.0001
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Students with Histories of Trauma in Libraries: A Collaboration of Accessibility and Library Services

Abstract: This paper explores methods for building relevant, accessible academic services in the context of a liberal arts college with a growing population of students with psychological disabilities. This work is situated in a learning commons, where academic-support programs, including accessibility services and library services, work collaboratively with a shared goal of getting students to access support earlier and more often in their college careers. The college is home to many students who identify as holding ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…, 1996; Sinnasamy and Karim, 2016). Additionally, in the disability community there is often a stigma attached to asking for help (Conley et al. , 2019), which is why library anxiety may be an even greater concern for individuals with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1996; Sinnasamy and Karim, 2016). Additionally, in the disability community there is often a stigma attached to asking for help (Conley et al. , 2019), which is why library anxiety may be an even greater concern for individuals with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no research focusing on library anxiety in individuals with disabilities, research does show that library anxiety is especially prevalent in marginalized populations (Jiao et al, 1996;Sinnasamy and Karim, 2016). Additionally, in the disability community there is often a stigma attached to asking for help (Conley et al, 2019), which is why library anxiety may be an even greater concern for individuals with disabilities. The findings of this study supported existing research suggesting library staff need better education and training on how to serve individuals with disabilities (Brannen et al, 2017;Koulikourdi, 2008;Pionke, 2020).…”
Section: Attitudinal Barriers Experienced In Librariesmentioning
confidence: 99%
“…Yan’s (2019) study proposes that the learning support services of university library in Canada include learning policy support, learning resource support, information literacy promotion support and learning ability cultivation, and learning space support. Other studies have found that university libraries not only play an important role in the course homework, examination, after-class extension study and self-improvement, but also provide innovative ideas for the discipline construction, educational quality, and educational mechanism (Chu and Sun, 2020; Conley et al, 2019). However, there are still many college students, especially for first-year students, who do not understand the nature and role of college libraries and librarians (Hughes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The librarian becomes essential in curating a suitable collection of books and educating teachers in their use. Self-service resources in both paper and digital formats provide even greater access for traumatized students who might avoid interaction with staff to acquire valuable information (Conley, Ferguson, & Kumbier, 2019). Doll and Doll (1997) discuss using bibliotherapy with children and teenagers from the perspective of a school librarian and a psychologist.…”
mentioning
confidence: 99%